Use of Complementary and Alternative Medicine for Epileptic Children in Tehran: A Cross-Sectional Study (2009-2011) - TONEKABONI, Seyed Hassan; JAFARI NAEINI, Sepideh; KHAJEH, Ali; YAGHINI, Omid; GHAZAVI, Ahad; ABDOLLAH GORJI*, Fatemeh (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Tonekaboni Sh, Jafari Naeini S, Khajeh A, Yaghini O, Ghazavi A, Abdollah Gorji F. Use of Complementary and Alternative Medicine for Epileptic Children in Tehran: A Cross-Sectional Study (2009-2011). Iran J Child Neurol. 2014 Winter; 8(1):26-31. Objective Although the use of Complementary and Alternative Medicine (CAM) has been evaluated globally, there are few studies in our country on this subject. The purpose of this study was to determine the prevalence, pattern of use, parental sources of information, and benefits of CAM in epileptic children in Tehran. Materials & Methods One hundred thirty-three parents or relatives of epileptic children who were referred to outpatient clinics or admitted in neurologic ward of four major hospitals in Tehran, were interviewed by our researcher based on a structured questionnaire; from 2009 to 2010. The information obtained comprised the demographic data of patients and their parents, frequency and morphology of convulsions, the type and sources of CAM and finally, the benefits and adverse effects of this practice. Results Forty-four percent of the respondents had used CAM methods either alone or in combination with other methods. The most frequently used CAM was written prayers followed by oral herbs and special diets. CAM was mainly introduced to them by relatives. Only 16.7% of these parents had discussed this matter with their children’s physicians. No efficacy to control seizure was observed for most of these methods. Conclusion This study showed that use of CAM in our study group is relatively common and may have a potentially hazardous role in the treatment process. So, it is necessary for physicians to have enough information about CAM practice in their patients. References: National Institutes of health. More than one third of US adults use complementary and alternative medicine, according to new government survey. [Serial online] 2004 (cited 2004 May 27). Available from: http://nccam. nih.gov/news/2004/052704.htm. Traditional Medicine: The Fifty-Sixth World Health Assembly WHO, 2003. World Health Organization, 2011. Available from: http://apps.who.int/gb/archive/ pdf_files/WHA56/ea56r31.pdf Michi CA. The use of herbal remedies in Jamaica. Ann Trop Paediatr 1992;12(1):31-6. Ricotti V, Delanty N. Use of complementary and alternative medicine in epilepsy. Curr Neurol Neurosci Rep 2006;6(4):347-53. Aburahma SK, Khader YS, Alzoubi k, Sawalha N. Complemetary and alternative medicine use in a pediatric neurology clinic. Complement Ther Chin Pract 2010;16(3):117-20. Eisenberg DM, Davis RB, Ettner SL, Appel S, Wilkey S, Van Rompay M, et al. Trends in alternative medicine use in United States, 1990-1997: results of a follow-up national survey. JAMA 1998;280(18):1569-75. Khonsari A, Gorji K, Abdollahpur F, Dehestani S, Mousavi A, Delfan B et al. Study of international approaches on treatment of common diseases using different methods of complementary medicine. J Ilam Uni Med Sci 2009;4:37-45. (Full text in Persian) Kwan P, Brodie MJ. Early identification of refractory epilepsy. N Engl J Med 20003;342(5):314-9. Oshikoya KA, Senbanjo IO, Njokanma OF, Soipe A. Use of complementary and alternative medicine for children with chronic health conditions in Lagos, Nigeria. BMC Complement Altern Med 2008;8:66. Liow K, Ablah E, Nguyen JC, Sadler T, Wolfe D, Tran KD et al. Pattern and frequency of use of complementary and alternative medicine among patients with epilepsy in the mid western United States. Epilepsy Behav 2007;10(4):576-82. Tehrani Banihashemi SA, Asgharifard H, Haghdoost AA, Barghamdi M, Mohammadhosseini N. The use of complementary/ Alternative medicine among the general population in Tehran /Iran. Payesh 2008;7(4):355-62.(Full text in Persian) Ekici B, That B, Abah S, Aydinli N, Ozmen M. Application of complementary and alternative medicine in epileptic children at a tertiary pediatric neurology center in Turkey. Eur J Integr Med 2011;4:e71-5. Soo I, Mah JK, Barlow K, Hamiwka L, Wirrell E. Use of complementary and alternative medical therapies in pediatric neurology clinic. Can J Neurol Sci 2005;32(4):524-28. Cuzzolin L, Zaffani S, Murgia V, Gangemi M, Meneghelli G, Chiamenti G, et al. Patterns and perceptions of complementary/alternative medicine among paediatricians and patients’ mothers: a review of the literature. Eur J Pediatr 2003;162(12):820-7.